2011
DOI: 10.1177/097215091101200204
|View full text |Cite
|
Sign up to set email alerts
|

East Asian Experience on Growth and Equity

Abstract: This article succinctly summarizes the growth experience of the four East Asian tiger economies (Hong Kong, Korea, Singapore and Taiwan) and three Association of South-East Asian Nations (ASEAN) states (Indonesia, Malaysia and Thailand). The crisis of 1997-98 had come to pass and the economies have returned to growth but not at the same tempo as in the earlier times. Several of the economies have experienced significantly reduced levels of poverty and visible inequalities. The degree of income inequality (meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Earlier attempts to formalize the definition of inclusive growth construe it as a measure of a combination of the growth of national income and income inequality (Ali & Son, 2007; Anand, Mishra, & Peiris, 2013). In the context of East Asia, Kolluru and Rao (2011) explored the linkages between growth and inequality, whereas the Indian experience has been accounted by Anand, Tulin and Kumar (2014). Although this approach is helpful in bringing together the two strands of poverty-inequality analysis and growth literature, it fails to capture the broader nature of the widely accepted connotations regarding inclusive growth.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier attempts to formalize the definition of inclusive growth construe it as a measure of a combination of the growth of national income and income inequality (Ali & Son, 2007; Anand, Mishra, & Peiris, 2013). In the context of East Asia, Kolluru and Rao (2011) explored the linkages between growth and inequality, whereas the Indian experience has been accounted by Anand, Tulin and Kumar (2014). Although this approach is helpful in bringing together the two strands of poverty-inequality analysis and growth literature, it fails to capture the broader nature of the widely accepted connotations regarding inclusive growth.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have been carried out to test convergence of the GDP of the countries in any regional block. Kolluru and Rao (2012) have examined the growth experience of the four East Asian economies, Hong Kong, Korea, Singapore and Taiwan, and three members of the Association of Southeast Asian Nations (ASEAN), Indonesia, Malaysia and Thailand. The study found that many economies have experienced reduction in the levels of poverty and inequalities.…”
Section: Introductionmentioning
confidence: 99%